Use of ICTs by Tribal Farmers for Obtaining Agricultural Information in Southern Rajasthan - Jat, Jeewan Ram; Punjabi, NK; Bhinda, Rashmi (Indian Journal of Extension Education, 2025)
Most of the tribal farmers of Southern Rajasthan are using ICT tools for seeking the agricultural information via mobile phones, television, radio, kisan call centre, information kiosks, internet and expert system. The study was conducted in Southern Rajasthan covering two districts (Banswara and Dungarpur) on the basis of availability of maximum facilities and infrastructures to promote use of ICT. Empirical data were collected personally from 160 farmers through a structured interview schedule. The results showed that majority of the farmers owned mobile phones as well as television and radio. The most frequently used ICT for social communication, contacting middle men for the marketing of produce and contacting experts on real time basis was mobile phone followed by television. The use of radio and kisan call centre was lower as compared to mobile phones and TV due to ICT availability and access levels being lower than other ICTs. Internet, touch screen computer and information kiosk and other application were still being rarely used by young and educated. Majority of the farmers (60.62%) were used the ICTs during the evening hours due to free and leisure time and telecast or broadcast of agricultural programs during the evening hours.